Non-Coding RNAs Operate in the Crosstalk Between Cancer Metabolic Reprogramming and Metastasis - Li, Ziyi; Sun, Xueying (Frontiers in Oncology, 2020)
Metastasis, the spread of cancer cells from a primary tumor to a secondary site, represents one of the hallmarks of malignancies and the leading cause of cancer-related death. The process of metastasis is a result of the interaction of genetic heterogeneity, abnormal metabolism, and tumor microenvironments. On the other hand, metabolic reprogramming, another malignancy hallmark, refers to the ability of cancer cells to alter metabolic and nutrient acquisition modes in order to support the energy demands for accomplishing the rapid growth, dissemination, and colonization. Cancer cells remodel metabolic patterns to supplement nutrients for their metastasis and also undergo metabolic adjustments at different stages of metastasis. Genes and signaling pathways involved in tumor metabolic reprogramming crosstalk with those participating in metastasis. Non-coding RNAs are a group of RNA molecules that do not code proteins but have pivotal biological functions. Some of microRNAs and lncRNAs, which are the two most extensively studied non-coding RNAs, have been identified to participate in regulating metabolic remodeling of glucose, lipid, glutamine, oxidative phosphorylation, and mitochondrial respiration, as well as the process of metastasis involving cell motility, transit in the circulation and growth at a new site. This article reviews recent progress on non-coding RNAs operating in the crosstalk between tumor metabolic reprogramming and metastasis, particularly those influencing metastasis through regulating metabolism, and the underlying mechanisms of how they exert their regulatory functions.